Approaching the world's religions. Volume 2, An evangelical theology of religions - Boyd, Robert (Eugene : Cascade Books, 2017)
Evangelical theology strives to be evangelical, conservative, and contemporary. In a world in which everyone is ""Christian,"" evangelical theology provides a balanced position between fundamentalism and liberalism. While theological debates within the family will occur, to be evangelical is a breath of fresh air for many. However, we do not live in such a world. We do find ourselves living in a secular, global society. It is secular because no religious organization dictates how we live our lives. It is global for at least two reasons. First, our technology brings us immediately in contact wi.
Description based upon print version of record.
Includes bibliographical references and index.
Master record variable field(s) change: 050, 072, 082, 650
Keywords: Religions; Religion -- Methodology; Religion -- Philosophy; Evangelicalism; RELIGION / Philosophy; Electronic books